2020
DOI: 10.1002/capr.12337
|View full text |Cite
|
Sign up to set email alerts
|

The dose‐effect model is good enough

Abstract: Although the effectiveness of psychotherapy is now widely recognised (e.g. American Psychological Association, 2013), questions about how much psychotherapy is necessary for client recovery remain. In response to these questions, two contemporary models of the association between the amount of treatment (number of sessions) and amount of change (in symptom distress) have emerged, each with supportive evidence. The first modelthe dose-effect (DE) model-was introduced by Howard and colleagues in the 1980s (Howar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(97 reference statements)
2
3
0
Order By: Relevance
“…In fewer than 10 sessions, ROS change estimates indicated that some clients experienced the same level of change as the average client who completed additional sessions. These results support the Good Enough Level (GEL) model, an idiographic description of psychotherapy processes (Barkham et al, 2006; Schuler et al, 2021). As described by Schuler et al (2021), the GEL model indicates that (a) clients who improve quickly will terminate sooner than those who evidence slower rates of change and (b) those who terminate sooner will experience the same amount of improvement as those who terminate later.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In fewer than 10 sessions, ROS change estimates indicated that some clients experienced the same level of change as the average client who completed additional sessions. These results support the Good Enough Level (GEL) model, an idiographic description of psychotherapy processes (Barkham et al, 2006; Schuler et al, 2021). As described by Schuler et al (2021), the GEL model indicates that (a) clients who improve quickly will terminate sooner than those who evidence slower rates of change and (b) those who terminate sooner will experience the same amount of improvement as those who terminate later.…”
Section: Discussionsupporting
confidence: 75%
“…These results support the Good Enough Level (GEL) model, an idiographic description of psychotherapy processes (Barkham et al, 2006; Schuler et al, 2021). As described by Schuler et al (2021), the GEL model indicates that (a) clients who improve quickly will terminate sooner than those who evidence slower rates of change and (b) those who terminate sooner will experience the same amount of improvement as those who terminate later. In the GEL model, while rate of change and length of treatment vary by client, outcomes remain the same.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…IRB granted a waiver of consent for disclosure of limited educational records with personally identifiable information removed. Examination of prominent models of psychotherapy within the context of trainee clinicians indicates that, on average, the largest amount of change is associated with early sessions in any given course of treatment (e.g., Callahan & Hynan, 2005; Schuler et al, 2021). Thus, trainee competency data anchored to the initiation of a course of treatment were selected for inclusion (rather than anchoring trainee competency data to termination of client’s course of treatment).…”
Section: Methodsmentioning
confidence: 99%
“…Given the high heterogeneity in individual responsiveness to psychotherapy (Baldwin et al, 2009;Barkham et al, 1996Barkham et al, , 2006, the number of CBT sessions should be predefined according to a fixed time frame, but must also leave room for flexible adaptation to the individual needs of patients who require more time to respond to psychotherapy (Bone et al, 2021;Falkenström et al, 2016). In this respect, future studies should also take into account the treatment setting in which psychotherapy takes place, as it may also influence change trajectories through various contextual factors (e.g., through financial and time constraints, Falkenström et al, 2016;Schuler et al, 2021). However, our results also suggest that longer treatments should be subject to a costbenefit assessment due to the less pronounced symptom improvement after 10 sessions and the high costs of psychotherapy.…”
Section: Discussionmentioning
confidence: 99%